2010
DOI: 10.1007/s00595-008-4051-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic enucleation of a gastroenteric duplication cyst arising in a pancreatic tail that did not communicate with the pancreatic duct: Report of a case

Abstract: Gastroenteric duplication rarely occurs in locations such as the pancreas. We report a case of gastroenteric duplication of the pancreatic tail, which was noncontiguous with the stomach and had no communication with the pancreatic duct, in a 3-year-old girl. The cyst was enucleated by laparoscopy, without the need for pancreatic resection. The optimal treatment procedures vary considerably, depending on where the gastroenteric duplication is located in the pancreas and, most importantly, whether there is commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…2 Only 57 documented cases of alimentary duplication occurring in connection with the pancreas have been reported so far. 3 Including our case, only 3 cases of intrapancreatic GDC have been reported so far. Moss et al reported the case of a 9-year-old child who presented with recurrent pancreatitis due to GDC within an aberrant pancreatic lobe near the neck of pancreas.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…2 Only 57 documented cases of alimentary duplication occurring in connection with the pancreas have been reported so far. 3 Including our case, only 3 cases of intrapancreatic GDC have been reported so far. Moss et al reported the case of a 9-year-old child who presented with recurrent pancreatitis due to GDC within an aberrant pancreatic lobe near the neck of pancreas.…”
Section: Discussionmentioning
confidence: 75%
“…Only 57 documented cases of alimentary duplication occurring in connection with the pancreas have been reported so far . Including our case, only 3 cases of intrapancreatic GDC have been reported so far.…”
Section: Discussionmentioning
confidence: 80%
“…The symptoms of a gastric duplication depend on the size and location of the cyst. The common symptoms are vomiting, an abdominal mass, and epigastric pain or discomfort 6…”
Section: Discussionmentioning
confidence: 99%
“…The detection of a multilayered structure of the cystic wall is diagnostic for a duplication cyst 7, 8. On CT, duplication cysts are seen as smoothly rounded, fluid‐filled cysts or tubular structures with thin or thick walls in or adjacent to the gastric wall 3, 6. Cystic wall calcifications have rarely been reported 9…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 4 patients with pancreatic head lesions, Siddiqui et al reported that local resection was appropriate management without the need for a more radical resection [8] . Other groups have also described the use of laparoscopy for the management of duplication cysts located in the tail of the pancreas [9] . We describe the presentation and management of 3 patients with gastric duplication cysts located in either the body or tail of the pancreas.…”
Section: Introduction ▼mentioning
confidence: 99%